Biology, ecology, and epidemiology of Alternaria species affecting tomato: ground information for the development of a predictive model - Salotti, Irene; Giorni, Paola; Battilani, Paola (Frontiers in Plant Science, 2024)
Among pathogens that affect tomato, Alternaria spp. are important due to their implications in yield losses and the contamination of tomato products by mycotoxins. In this study, a systematic literature review was conducted to retrieve and analyze available data on the Alternaria-tomato pathosystem, with particular attention focused on the main biological processes included in the pathogen life cycle and mycotoxin production. We considered 110 papers (selected from initial 2,138 papers) on five Alternaria species that were historically related or recently identified to cause damage to tomato leafage and fruits. Published mathematical models related to Alternaria diseases in tomato were also screened based on their aim and development methods, highlighting the wide use of empirical approach. Retrieved information was also evaluated for applications in building a mechanistic, weather-driven model that incorporates the key steps of the pathogen life cycle. This systematic review highlights several knowledge gaps, including the effect of wetness on infection and environmental requirements for mycotoxin production, and suggests paths for further research especially for recently isolated species.